P3-8: Eye Position Distribution Depending on Head Orientation in Natural Scene Viewing - Ryoichi Nakashima; Yu Fang; Kazumichi Matsumiya; Rumi Tokunaga; Ichiro Kuriki; Satoshi Shioiri (i-Perception, 2012)
We usually move our body and head as well as eyes in order to obtain information from visual environments. Although several studies reported the coordination between eye and head movements, most of them used simple stimuli and/or conditions. In this study, we investigated relationships between eye movements and head orientations while viewing natural scene images in a large size of screen. We measured participants' eye positions and head orientations simultaneously during a natural scene image viewing (each image subtended about 53 × 41 deg), in which the participant on a chair moved their head and eyes naturally for 5 s. We analyzed the eye- and head-movement data to obtain frequency distribution of eye position as a function of head orientation. The results showed a clear correlation between horizontal eye position and horizontal head orientation. When the head pointed to the left or right, the peak frequency of eye position shifted also to the left or right (relative to the head), respectively, and when the head was centered, the peak of the frequency distribution for the eye position was also centered in the head. These results are consistent with our previous study in which a visual search task was performed (visual search for “T” among “L”s). In contrast, no correlation was found between vertical direction between the eye positions and head orientations. These findings suggest that the mechanism of head-eye coordination may function only horizontally at least under the present condition.